2014
DOI: 10.1108/aaaj-04-2013-1313
|View full text |Cite
|
Sign up to set email alerts
|

Integrated reporting: On the need for broadening out and opening up

Abstract: Purpose-The purpose of this paper is to critically assess integrated reporting so as to "broaden out" and "open up" dialogue and debate about how accounting and reporting standards might assist or obstruct efforts to foster sustainable business practices. Design/methodology/approach-The authors link current debates about integrated reporting to prior research on the contested politics of social and environmental reporting, and critiques of the dominance of business case framings. The authors introduce research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
370
1
27

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(408 citation statements)
references
References 85 publications
(122 reference statements)
10
370
1
27
Order By: Relevance
“…New mandatory reporting rules in Europe (Directive 2014/95/EU) and stock exchange listing rules in, inter alia, Singapore, Kuala lumpur and Copenhagen also require companies to disclose non-financial information (still not necessarily integrated with financial information). however some authors (Brown and Dillard, 2014) suggest that overcoming shortcomings of the dominating neoliberal doctrine is not just the matter of introduction of mandatory regulations. As it has been argued in the proposed model coercive pressures have little impact on the diffusion of strategic or systemic modes of CSR.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…New mandatory reporting rules in Europe (Directive 2014/95/EU) and stock exchange listing rules in, inter alia, Singapore, Kuala lumpur and Copenhagen also require companies to disclose non-financial information (still not necessarily integrated with financial information). however some authors (Brown and Dillard, 2014) suggest that overcoming shortcomings of the dominating neoliberal doctrine is not just the matter of introduction of mandatory regulations. As it has been argued in the proposed model coercive pressures have little impact on the diffusion of strategic or systemic modes of CSR.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Rensburg and Botha (2014) demonstrated that integrated reports were taken as additional disclosures and these reports were taken or used as the main source of information by the very limited number of providers of financial capital. Many studies have addressed the needs of <IR> (Brown and Dillard, 2014;Cheng et al, 2014;Villiers et al, 2014;Adams, 2015). Lee and Yeo (2016) asserted that the benefits of this reporting exceed its costs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are several reasons for this. The <IR> framework, for instance, has received widespread criticism for being "one-sided" and "limited" [54,55]. In 2014, Haller and van Staden also argued that for the application of the concept of integrated reporting at the corporate level using the <IR> framework is not sufficient [56].…”
Section: Methodsmentioning
confidence: 99%